Corporate Reputation and Corporate Image - Empirical Analysis on the Example of Polish Banking Sector - Danuta Szwajca (Institute of Economic Research (IER), 2017)
Corporate reputation and image are two valuable intangible resources of the company, aimed at building its long-term competitive advantage and market value. Although reputation and image are interrelated categories, they should not be identified with each another. The differences are not only in the definition and character, but also in the mechanism of formation and tools to create these resources by the company. Image is a picture, perceptions and associations about the company in the minds of consumers, which may be created using the tools of PR and advertising in a relatively short period of time. Reputation is a review of the company and its activities, formulated by various stakeholder groups on the basis of not only the advertising, but also on the basis of the assessment of real activities of companies in the long term. The cognitive objective of the article is to point out the fundamental differences between reputation and image on the basis of the analysis of approaches and theoretical concepts. The practical objective is to make an attempt to identify the differences and relationships between reputation and image on the basis of empirical analysis, therefore the research was conducted in the Polish banking sector. In order to evaluate the image and reputation, the survey method was used aimed at the customers of banks operating on the Polish market. The results allowed formulating the thesis that the banks that are characterized by a consistent, unambiguous and positive image have higher rates of reputation. Due to some limitations of research conducted, mainly concerning the size and methods of sampling as well as the method applied for measuring the corporate reputation and image, the relationships identified should be treated as a starting point for broader research and for conducting further discussions in this area.
Keywords: G21; L14; L25; M31; 330; corporate reputation; corporate image; intangible resources; banking sector